The Association Between Presenting Visual Impairment, Health, and Employment Status. (May 2021) - McDonnall, Michele C.; McKnight, Zhen S.
Introduction: The purpose of this study was to investigate the effect of visual impairment and correctable visual impairment (i.e., uncorrected refractive errors) on being out of the labor force and on unemployment. The effect of health on labor force status was also investigated. Method: National Health and Nutrition Examination Survey (NHANES) data from 1999 to 2008 ( N = 15, 650) was used for this study. Participants were classified into three vision status groups: normal, correctable visual impairment, and visual impairment. Statistical analyses utilized were chi-square and logistic regression. Results: Having a visual impairment was significantly associated with being out of the labor force, while having a correctable visual impairment was not. Conversely, having a correctable visual impairment was associated with unemployment, while having a visual impairment was not. Being out of the labor force was not significantly associated with health for those with a visual impairment, although it was for those with correctable visual impairments and normal vision. Discussion: Given previous research, it was surprising to find that health was not associated with being out of the labor force for those with visual impairments. Perhaps other disadvantages for the people with visual impairments identified in this study contributed to their higher out-of-the-labor-force rates regardless of health. Implications for practitioners: Researchers utilizing national data sets that rely on self-reports to identify visual impairments should realize that some of those who self-identify as being visually impaired may actually have correctable visual impairments. Current research is needed to understand why a majority of people with visual impairments are not seeking employment and have removed themselves from the labor force.